Задание № 1
![x^{2}+6x+5=x^{2}+x+5x+5=(x^{2}+x)+(5x+5)=x(x+1)+5(x+1)=(x+1)(x+5) x^{2}+6x+5=x^{2}+x+5x+5=(x^{2}+x)+(5x+5)=x(x+1)+5(x+1)=(x+1)(x+5)](https://tex.z-dn.net/?f=x%5E%7B2%7D%2B6x%2B5%3Dx%5E%7B2%7D%2Bx%2B5x%2B5%3D%28x%5E%7B2%7D%2Bx%29%2B%285x%2B5%29%3Dx%28x%2B1%29%2B5%28x%2B1%29%3D%28x%2B1%29%28x%2B5%29)
======================================================================
![x^{2}-x-6=x^{2}+2x-3x-6=(x^{2}+2x)+(-3x-6)=(x^{2}+2x)-(3x+6)=x(x+2)-3(x+2)=(x+2)(x-3) x^{2}-x-6=x^{2}+2x-3x-6=(x^{2}+2x)+(-3x-6)=(x^{2}+2x)-(3x+6)=x(x+2)-3(x+2)=(x+2)(x-3)](https://tex.z-dn.net/?f=x%5E%7B2%7D-x-6%3Dx%5E%7B2%7D%2B2x-3x-6%3D%28x%5E%7B2%7D%2B2x%29%2B%28-3x-6%29%3D%28x%5E%7B2%7D%2B2x%29-%283x%2B6%29%3Dx%28x%2B2%29-3%28x%2B2%29%3D%28x%2B2%29%28x-3%29)
======================================================================
![a^{2}-5a+4=a^{2}-a-4a+4=(a^{2}-a)+(-4a+4)=(a^{2}-a)-(4a-4)=a(a-1)-4(a-1)=(a-1)(a-4) a^{2}-5a+4=a^{2}-a-4a+4=(a^{2}-a)+(-4a+4)=(a^{2}-a)-(4a-4)=a(a-1)-4(a-1)=(a-1)(a-4)](https://tex.z-dn.net/?f=a%5E%7B2%7D-5a%2B4%3Da%5E%7B2%7D-a-4a%2B4%3D%28a%5E%7B2%7D-a%29%2B%28-4a%2B4%29%3D%28a%5E%7B2%7D-a%29-%284a-4%29%3Da%28a-1%29-4%28a-1%29%3D%28a-1%29%28a-4%29)
======================================================================
![a^{2}-6a-16=a^{2}+2a-8a-16=(a^{2}+2a)+(-8a-16)=(a^{2}+2a)-(8a+16)=a(a+2)-8(a+2)=(a+2)(a-8) a^{2}-6a-16=a^{2}+2a-8a-16=(a^{2}+2a)+(-8a-16)=(a^{2}+2a)-(8a+16)=a(a+2)-8(a+2)=(a+2)(a-8)](https://tex.z-dn.net/?f=a%5E%7B2%7D-6a-16%3Da%5E%7B2%7D%2B2a-8a-16%3D%28a%5E%7B2%7D%2B2a%29%2B%28-8a-16%29%3D%28a%5E%7B2%7D%2B2a%29-%288a%2B16%29%3Da%28a%2B2%29-8%28a%2B2%29%3D%28a%2B2%29%28a-8%29)
======================================================================
Задание № 2
![ac^{2}-ad+c^{3}-cd-bc^{2}+bd=(-ad-cd+bd)+(ac^{2}+c^{3}-bc^{2})=-(ad+cd-bd)+(ac^{2}+c^{3}-bc^{2})=-d(a+c-b)+c^{2}(a+c-b)=(a+c-b)(c^{2}-d) ac^{2}-ad+c^{3}-cd-bc^{2}+bd=(-ad-cd+bd)+(ac^{2}+c^{3}-bc^{2})=-(ad+cd-bd)+(ac^{2}+c^{3}-bc^{2})=-d(a+c-b)+c^{2}(a+c-b)=(a+c-b)(c^{2}-d)](https://tex.z-dn.net/?f=ac%5E%7B2%7D-ad%2Bc%5E%7B3%7D-cd-bc%5E%7B2%7D%2Bbd%3D%28-ad-cd%2Bbd%29%2B%28ac%5E%7B2%7D%2Bc%5E%7B3%7D-bc%5E%7B2%7D%29%3D-%28ad%2Bcd-bd%29%2B%28ac%5E%7B2%7D%2Bc%5E%7B3%7D-bc%5E%7B2%7D%29%3D-d%28a%2Bc-b%29%2Bc%5E%7B2%7D%28a%2Bc-b%29%3D%28a%2Bc-b%29%28c%5E%7B2%7D-d%29+)
======================================================================
![ax^{2}+ay^{2}-bx^{2}-by^{2}+b-a=ax^{2}-bx^{2}+ay^{2}-by^{2}-a+b=(ax^{2}-bx^{2})+(ay^{2}-by^{2})+(-a+b)=(ax^{2}-bx^{2})+(ay^{2}-by^{2})-(a-b)=x^{2}(a-b)+y^{2}(a-b)-1(a-b)= (a-b)(x^{2}+y^{2}-1) ax^{2}+ay^{2}-bx^{2}-by^{2}+b-a=ax^{2}-bx^{2}+ay^{2}-by^{2}-a+b=(ax^{2}-bx^{2})+(ay^{2}-by^{2})+(-a+b)=(ax^{2}-bx^{2})+(ay^{2}-by^{2})-(a-b)=x^{2}(a-b)+y^{2}(a-b)-1(a-b)= (a-b)(x^{2}+y^{2}-1)](https://tex.z-dn.net/?f=ax%5E%7B2%7D%2Bay%5E%7B2%7D-bx%5E%7B2%7D-by%5E%7B2%7D%2Bb-a%3Dax%5E%7B2%7D-bx%5E%7B2%7D%2Bay%5E%7B2%7D-by%5E%7B2%7D-a%2Bb%3D%28ax%5E%7B2%7D-bx%5E%7B2%7D%29%2B%28ay%5E%7B2%7D-by%5E%7B2%7D%29%2B%28-a%2Bb%29%3D%28ax%5E%7B2%7D-bx%5E%7B2%7D%29%2B%28ay%5E%7B2%7D-by%5E%7B2%7D%29-%28a-b%29%3Dx%5E%7B2%7D%28a-b%29%2By%5E%7B2%7D%28a-b%29-1%28a-b%29%3D+%28a-b%29%28x%5E%7B2%7D%2By%5E%7B2%7D-1%29)